# 1 Solve for x log2 (x+3) + log 2 (x 3)=42 solvelog2(3x 2)=

Content type
User Generated
Rating
Showing Page:
1/2
1. Solve for x
log2 (x+3) + log 2 (x-3)=4
2. solve
log2(3x-2)=1
3. evaluate the expression
log375249
Solution
1. Solve for x
log2 (x+3) + log 2 (x-3)=4
(x+3)(x-3) = 2^4 = 16
x^2-9 = 16
x^2 = 9+16 = 25
x = sqrt(25)
x = 5
2. solve
log2(3x-2)=1
3x-2 = 2^1 = 2
3x = 2+2 = 4
x = 4/3

Showing Page:
2/2

Unformatted Attachment Preview
1. Solve for x log2 (x+3) + log 2 (x-3)=4 2. solve log2(3x-2)=1 3. evaluate the expression log375249 Solution 1. Solve for x log2 (x+3) + log 2 (x-3)=4 (x+3)(x-3) = 2^4 = 16 x^2-9 = 16 x^2 = 9+16 = 25 x = sqrt(25) x = 5 2. solve log2(3x-2)=1 3x-2 = 2^1 = 2 3x = 2+2 = 4 x = 4/3 3. evaluate the expression log375249 =2.37219263037181 Name: Description: ...
Purchase document to see full attachment
User generated content is uploaded by users for the purposes of learning and should be used following Studypool's honor code & terms of service.

### Review

Anonymous
I was having a hard time with this subject, and this was a great help.

Studypool
4.7
Indeed
4.5
Sitejabber
4.4